2011
DOI: 10.1016/j.mce.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone induces expression of the prolactin receptor gene through cooperative action of Sp1 and C/EBP

Abstract: Prolactin (Prl) and progesterone (P) cooperate synergistically during mammary gland development and tumorigenesis. We hypothesized that one mechanism for these effects may be through mutual induction of receptors (R). EpH4 mouse mammary epithelial cells stably transfected with PR-A express elevated levels of PrlR mRNA and protein compared to control EpH4 cells that lack the PR. Likewise, T47D human breast cancer cells treated with P overexpress the PrlR and activate PrlR promoter III. PrlR promoter III does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 48 publications
1
19
0
1
Order By: Relevance
“…In one series of studies, C/EBPβ was found to be necessary for appropriate prolactin and steroid signalling in mouse mammary glands [149]. In a cell-free in vitro binding assay, as well as after transfection of ERα-negative MDA-MB-231 breast cancer cells with ERα and C/EBPβ, ERα was found to form a complex with SP1 and C/EBPβ that is required for the oestrogen-and progesterone-induced expression of PRLR mRNA in EpH4 normal mouse mammary cells [150,151].…”
Section: C/ebpβ and Endocrine Hormonesmentioning
confidence: 99%
“…In one series of studies, C/EBPβ was found to be necessary for appropriate prolactin and steroid signalling in mouse mammary glands [149]. In a cell-free in vitro binding assay, as well as after transfection of ERα-negative MDA-MB-231 breast cancer cells with ERα and C/EBPβ, ERα was found to form a complex with SP1 and C/EBPβ that is required for the oestrogen-and progesterone-induced expression of PRLR mRNA in EpH4 normal mouse mammary cells [150,151].…”
Section: C/ebpβ and Endocrine Hormonesmentioning
confidence: 99%
“…n.s., not significant. tion with other transcription factors, such as activator protein 1 NF-B, through a tethering mechanism (53)(54)(55)(56). To assess the whole cellular effect of K464Q mutation, we generated multiple clones of stably transfected pcDNA3.1, WT PRB, PRB-K464Q, and PRB-K464F MDA-MB-231 cells, and three clones of similar levels of PR protein (Fig.…”
Section: Lys-464 Mutations Alter Markedly Pr-mediated Progestin Respomentioning
confidence: 99%
“…There is significant crosstalk between prolactin (PRL) and P in the mouse mammary gland, with many of the same genes regulated by both hormones, possibly coregulated by STAT5 (Fernandez-Valdivia et al , 2008; Goldhar et al , 2011; Hilton et al ). In human breast cancer cells both liganded and unliganded PRs upregulate PRL receptors (PRLR) (Jacobsen et al , 2002; Tseng & Zhu, 1998).…”
Section: Detailed Promoter Analyses and Pr Isoformsmentioning
confidence: 99%
“…In human breast cancer cells both liganded and unliganded PRs upregulate PRL receptors (PRLR) (Jacobsen et al , 2002; Tseng & Zhu, 1998). The PRLR promoter lacks a consensus PRE but contains multiple transcription factor binding sites including ones for CEBPβ, SP1 and AP1 (Hu et al , 1998) all of which interact with PR (Goldhar et al , 2011). In normal mouse epithelial cells, P regulate inhibitor of differentiation 4 (ID4) via PRB.…”
Section: Detailed Promoter Analyses and Pr Isoformsmentioning
confidence: 99%